Mathematical models of economic growth - Tinbergen, Jan.; Bos, Hendricus Cornelis (New York : McGraw-Hill, 1962)
This book is an attempt at presenting, in simple mathematical form, a number of development models which may be of practical use in development planning.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Economics---Mathematical models; Economics, Mathematics